Knowledge and Attitude of Saudi Health Professions' Students Regarding Patient's Bill of Rights - Salwa B. El-Sobkey; Alyah M. Almoajel; May N. Al-Muammar (Kerman University of Medical Sciences, 2014)
Background Patient's rights are worldwide considerations. Saudi Patient's Bill of Rights (PBR) which was established in 2006 contained 12 items. Lack of knowledge regarding the Saudi PBR limits its implementation in health facilities. This study aimed to investigate the knowledge of health professions' students at College of Applied Medical Sciences (CAMS) Riyadh Saudi Arabia regarding the existence and content of Saudi PBR as well as their attitude toward its ineffectiveness. Method A 3-parts survey was used to collect data from 239 volunteer students participated in the study. Data were analyzed by descriptive and analytical statistics using SPSS. Results Results showed that although the majority of students (96.7%) believe in the ineffectiveness of patient's rights, half (52.3%) of them had perceptual knowledge regarding the existence of Saudi PBR and only 7.9% of them were knowledgeable about some items (1-4 items) of the bill. Privacy and confidentiality of patient was the most common known patient's rights. Students' academic level was not correlated to neither their knowledge regarding the bill existence or its content nor to their attitude toward the bill. The majority of the students (93%) reported that only one course within their curriculum was patient's rights-course related. About one quarter (23.4%) of the students reported that teaching staff used to mention patient's rights in their teaching sessions. Conclusion The Saudi health professions students at CAMS have positive attitude toward the ineffectiveness of patient's rights nevertheless they showed limited knowledge regarding the existence of Saudi PBR and its contents. CAMS curriculums do not support the subject of patient's rights.